PENGELOLAAN RISIKO DALAM ERA DIGITAL: STRATEGI UNTUK MENINGKATKAN KETAHANAN ORGANISASI - kamilah, nila farchatul (Maliki Interdisciplinary Journal, 2025)
The development of information and communication technology has driven significant transformation in Islamic banking operations, presenting opportunities for innovation as well as new and increasingly complex risk challenges in the digital era. This article discusses the importance of adaptive and integrated digital risk management to improve organizational resilience amid technological disruption. Risk management focuses not only on mitigating threats, but also on creating added value through the utilization of digital opportunities. An effective strategy involves the integration of advanced technologies such as artificial intelligence, big data, and blockchain, the implementation of international risk management standards, and the strengthening of an innovative organizational culture and continuous learning. In addition, transformational leadership and the development of digital literacy of human resources are key factors in building organizational resilience. With a proactive and collaborative approach, organizations can improve competitiveness and operational sustainability amidst the evolving digital dynamics.